Science of adaptation to climate change and science for adaptation - Swart, Rob; Biesbroek, Robbert; Lourenço, Tiago Capela (Frontiers in Environmental Science, 2014)
Adaptation to climate change has gained a prominent place next to mitigation on global, national and local policy agendas. However, while an abundance of adaptation strategies, plans and programmes have been developed, progress in turning these into action has been slow. The development of a sound knowledge basis to support adaptation globally is suggested to accelerate progress, but has lagged behind. The emphasis in both current and newly proposed programmes is very much on practice-oriented research with strong stakeholder participation. This paper supports such practice-oriented research, but argues that this is insufficient to support adaptation policy and practice in a productive manner. We argue that there is not only a need for science for adaptation, but also a science of adaptation. The paper argues that participatory, practice-oriented research is indeed essential, but has to be complemented by and connected to more fundamental inquiry and concept development, which takes into account knowledge that has been developed in disciplinary sciences and on issues other than climate change adaptation. At the same time, the level and method of participation in science for adaptation should be determined on the basis of the specific project context and goals. More emphasis on science of adaptation can lead to improved understanding of the conditions for successful science for adaptation.